Orbital Cysticercosis – masquerading as preseptal cellulitis with ptosis - Raj, Amit; Arya, Sudesh Kumar; Topiwala, Pratik; Gupta, Panchmi; Sood, Sunandan (Nepalese Journal of Ophthalmology, 2016)
We are sharing a case of orbital cysticercosis,which presented to us initially with simple ptosis and later on with upper lid inflammation and restricted ocular motility in upgaze. Human cysticercosis, a parasitic infection caused by Cysticercus cellulosae, the larval form of the cestode, Taenia solium, is a benign infection of the subcutaneous tissues, inter-muscular fascia, muscles and other organs. Though it exists worldwide, it is more prevalent in the developing countries of Latin America, Asia and Africa, especially in areas where under-cooked pork is consumed regularly (Pushker et al, 2001). However, 5 year study of 33 cases of Ocular/Adnexal cysticercosis showed seventy percent of patients were of low socioeconomic group and 70% were strictly vegetarians (Atul et al, 1995). The clinical manifestation of orbital cysticercosis is entirely different from neuro-cysticercosis or cysticercosis of other parts of body. Diagnosis of cysticercosis is mainly based on highly specific radiological signs and history of exposure in endemic areas.